IMPROVING THE EIGHTH GRADE STUDENTS’ WRITING COMPETENCY THROUGH PERSONAL PHOTOGRAPH TECHNIQUE AT SMPN 3 SINGARAJA ACADEMIC YEAR 2014/2015 - Darma, I Gede Susila; Tantra, Dw. Kmg.; Padmadewi, Ni Nym. (Universitas Pendidikan Ganesha, 2018)
Abstract This for achievements in each indicator of writing competency of the eighth grade students in SMP N 3 Singaraja after applying the personal photograph technique in academic year 2014/2015. To know the achievements in each indicator of writing competencies of the eighth grade students in SMP N 3 Singaraja after applying the personal photograph technique in academic year 2014/2015. There are 30 students in 15 male and 15 female students in especially VIIIE in SMP N 3 Singaraja. The studies have had two cycles where each cycle consists of planning, action, observation and reflection. There are two types of data to analyze the data that was both qualitative and quantitative data. In preliminary observation based on general text: 22 (73.3%), in text type’s descriptive text 26 (86.7%), recount text 24(80%) had problem. For this in indicator descriptive text such as: authenticity 22(73%), title suitability 12(40%), text structure 19 (63%), diction 13(43%), grammar 22(73%), neatness 18(60%), writing competency 21(70%).Recount text such as: authenticity: 17(57%),title suitability 18(60%),text structure 18(60%),diction 14(47%), grammar 18(60%), neatness 18(60%), writing competency 20(67%). In cycle I based on general text: 12 (40%), in text type such as: descriptive text 18(60%), recount text 13(43%) and in each indictor for descriptive text such as: authenticity 1(3%), title suitability 3(10%), text structure 2(7%), diction 6 (20%), grammar 5(17%), neatness 1(3%), writing competency 5(17%). Recount test such as: 9(3%), 9(3%), 10(3.3%), 9(3%), 10(3.3%), 4 (13%). For the cycle II based on general text: 9(30%), in text type such as: descriptive text 9(30%) and recount text 3(10%). In each indicator of writing skill such as: authenticity 2(7%), title suitability 3(10%), text structure 1(3%), diction 4(13%), grammar 2(7%), neatness 3(10%), writing competency 1(3%). Recount text such as: 2(7%), 3(10%), 1(3%), 3(10%), 1(3%), 4(13%), 5(17%).Learning from an impressive improvement of the technique in writing at SMPN 3 Singaraja, teachers are suggested to make use of contextual and real life media.Key words: Personal Photograph Technique, writing competency